The features of state and municipal management of the development of single-industry settlements in the Arctic zone of the Russian Federation - Evgeniy E. Plisetskiy; Ekaterina A. Malitskaya (Northern Arctic Federal University, 2017)
The article considers the current system of management of the development of single-industry settlements in the Arctic zone of the Russian Federation, the tools of strategic and program-target management of the development of single-industry cities are analyzed which are used at the state and municipal levels, the suggestions for improving the system of management of the Arctic cities are made. This system should consider both the specific character of development of each city, and to be linked with the ongoing government policy, the interests of local authorities, business and local communities. The methodology is based on the use of search and economic-statistical methods, method of comparative analysis. The main recommendations are the formation of a strategic vision for the development of promising sectors (types of economic activities) in monotowns, introduction of program-target management in the strategic planning of complex investment plans of monotowns, and elaboration of the concept of the informational platform of investment projects in single-industry cities.